CHOICE OF FORUM DALAM PENYELESAIAN SENGKETA PERBANKAN SYARIAH PASCA TERBITNYA PUTUSAN MAHKAMAH KONSTITUSI NO.93/PUU-X/2012 - Yunari, Afrik (Ahkam: Jurnal Hukum Islam, 2016)
The dispute resolution process which emerges after the issue of theIslamic Banking Law No. 21/2008, has led to occurrence of disputesettlement or contention regarding to the institution for the disputeresolution. The dispute occurs between the Basyarnas with the DistrictCourt or between Basyarnas with Religious Courts or between theReligious Courts with the District Court. This problem occurs due tolegal clarification of Article 55, Paragraph 2 issued by the ConstitutionCourt, which confirms that the article is against the Constitution andhas no binding legal force. This study discusses the possible alternativeof dispute settlement forum in Islamic banking after the publicationof the legal decision of the Constitution Court No. 93/PUU-X/2012,discuss the sharia banking dispute resolution before and after theinception of Act No. 21/ 2008 about Islamic banking, the legal decisionof the Constitution Court No. 93/PUU-X/2012, and the choice ofdispute settlement forum in Islamic banking after publication of thelegal decision of the Constitution Court No. 93/PUU-X/2012.Kata kunci: Choice of Forum, Sengketa Perbankan Syariah, MK No.93/PUU-X/2012